2009
DOI: 10.1002/jmri.21766
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐based large deformation high dimensional mapping of the hippocampus in rats: Development and validation of the technique

Abstract: Purpose:To report the detection of structural and functional biological changes in living animals using small animal in vivo MRI that complements traditional ex vivo histological techniques. We report the development and validation of the application of large deformation high dimensional mapping (HDM-LD) segmentation for the hippocampus in the rat. Materials and Methods:High resolution volumetric T2 weighted MRI images were acquired at 4.7 Tesla from six male in-breed nonepileptic Wistar rats. Two HDM-LD segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Our section (700 μm in thickness) induced a partial volume effect. By comparison, Wolf et al reported a hippocampal volume of about 100 mm 3 (section thickness 600 μm) (Wolf et al, 2002) and (Hogan et al, 2009) about 74 mm 3 (section thickness 500 μm), while we obtained about 117 mm 3 (700 μm). However, Kalisch et al (2006) and Driscoll et al (2006) reported a change in hippocampal volume using similar MRI parameters (section thickness 750 μm and 1 mm) in a rat model of anxiety and in aging rats, respectively.…”
Section: Discussionsupporting
confidence: 43%
“…Our section (700 μm in thickness) induced a partial volume effect. By comparison, Wolf et al reported a hippocampal volume of about 100 mm 3 (section thickness 600 μm) (Wolf et al, 2002) and (Hogan et al, 2009) about 74 mm 3 (section thickness 500 μm), while we obtained about 117 mm 3 (700 μm). However, Kalisch et al (2006) and Driscoll et al (2006) reported a change in hippocampal volume using similar MRI parameters (section thickness 750 μm and 1 mm) in a rat model of anxiety and in aging rats, respectively.…”
Section: Discussionsupporting
confidence: 43%
“…Although these subtle findings reached statistical significance, we interpret them cautiously given that no other measures in the study comparing the epileptic and nonepileptic groups identified differences. Nonetheless, the strength of HDM‐LD and multivariate logistic regression analyses is their ability to detect subtle findings (Csernansky et al., ; Hogan et al., ). Therefore, the differences reported herein may indicate hippocampal abnormalities that occur at various time points post‐TBI that are involved in PTE.…”
Section: Discussionmentioning
confidence: 99%
“…Large‐deformation high‐dimensional mapping (HDM‐LD) of hippocampal morphometry was also completed as described previously (Hogan et al., ; Liu et al., ). HDM‐LD utilizes computer‐assisted shape recognition to identify patterns within MRI data (Bouilleret et al., ; Hogan et al., ). Computational anatomic techniques produce three‐dimensional surface representations of the hippocampus with resolution at a subvoxel level, enabling visualization of details of hippocampal surface anatomy (Gardner & Hogan, ).…”
Section: Methodsmentioning
confidence: 99%
“…HDM-LD utilizes the power of computer-assisted shape recognition to identify patterns within image data (16,17). Computational anatomic techniques produce 3-dimensional surface representations of the hippocampus with resolution at a subvoxel level, enabling visualization of details of hippocampal surface anatomy (18).…”
Section: Large-deformation High-dimensional Mapping (Hdm-ld) Of Hippomentioning
confidence: 99%
“…Changes in morphology can be detected even when total hippocampal volume changes are not significantly different (19)(20)(21)(22), using either visual analysis of deformation surfaces or multivariate ANOVA on the coefficients from eigenvector fields (23). Originally developed for human studies, this method has been adapted and validated for the assessment of rat hippocampus (16,17). Methods for comparing groups were as previously described (16).…”
Section: Large-deformation High-dimensional Mapping (Hdm-ld) Of Hippomentioning
confidence: 99%